Microanatomy and histology of the distal limb elements of ophthalmosaurids from the Middle Jurassic to the Lower Cretaceous of the Neuqu en Basin, Patagonia, Argentina - Talevi, Marianella (2020)
Fil: Talevi, Marianella. Universidad Nacional de Río Negro. Instituto de Investigación en Paleobiología y Geología. Río Negro, Argentina.